Insomnia Selama Pandemi COVID-19 - Devi Yulia Putri Haryanti (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
COVID-19 is a new disease that has become a global pandemic. The spread that is very fast around the world and various manifestations clinics make people afraid of infection SARS-CoV-2. This can affect the quality and sleep patterns of people, which can lead to insomnia. The purpose of this article is to determine the impact of COVID-19 on the incidence of insomnia in society. The method used is a systematic literature review on 18 articles published from the NCBI website, Google Scholar, Elsevier, and the website WHO. The result of this literature review is that the COVID-19 pandemic has an impact on the incidence of insomnia in the community and worsens the symptoms of patients who have been diagnosed with insomnia. This happened because of people's fear of COVID-19 disease. Besides, there have been many changes to people's daily routines during the COVID-19 pandemic which have affected the incidence of insomnia.